Emergent strategies for e-business processes, services, and implications advancing corporate frameworks - Lee, In, 1958-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book presents a collection of research associated with the emerging e-business technologies and applications, attempting to stimulate the advancement of various e-business frameworks and applications, and to provide future research directions"--Provided by publisher.
Section IV: Online consumer behavior. 13. Socio-economic impacts of offshore outsourcing of information technology / Karl Knapp, Sushil Sharma, Kevin King -- 14. Towards theory development for emergent e-business innovations / Indrit Troshani -- 15. An introduction to the management and protection of intellectual property rights / Bill Vassiliadis -- 16. Intelligent contracting / Tagelsir Gasmelseid -- 17. The applicability of network effect theory to low-cost adoption decisions / Jaeki Song, Eric Walden -- 18. An empirical analysis of cellular phone users' convenience perception and its impact on shopping intention in mobile commerce / Wen-Jang Jih -- 19. The effects of system features, perceived risk and benefit, and customer characteristics on online bill paying / Fang He.
"Premier reference source"--Cover.
Includes bibliographical references (p. 347-386) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 28, 2010).
Keywords: Electronic commerce; B2C service markets; Business model development; Convergent interviewing; Customer characteristics; E-business management; E-business models; E-consumer relationship management; E-CRM analysis; E-health systems; Emergent e-business innovations; E-supply chain management perspective; Intellectual property rights; Intelligent contracting; Managerial discretion and e-CRM performance; Multi-channel retailing; Network effect theory; Offshore outsourcing of information technology; Online consumer behavior; Reverse auction-based e-business model; Theory development; Electronic books